Heteronormativity in BL Webtoons Love is an Illusion, Room to Room, and Path to You - Agnes Katarina Candra Dewi; Jenny Mochtar (Institute of Research and Community Outreach - Petra Christian University, 2021)
This study exploring three BL Webtoons is for taking a closer look on how the characteristics of heterosexuality can be found in BL Webtoons. To achieve that purpose, the theories used cover the set formula of male and female illustrations and gender roles. The first analysis is about the physical appearance by going into details of the physical build, facial features, and biology of the masculine and feminine males. The second one is the actions to see the feminine and masculine characters’ different ways of acting and thinking. The result of the analysis reveals how feminine males in these three BL Webtoons are depicted the same way as females are. The fact that gender identity and gender roles that describe heterosexuality are present, shows that these three BL Webtoons are narrated in the framework of heterosexuality. So, heteronormativity, the view that heterosexuality is the default, succeeds in infiltrating BL Webtoons. Keywords: BL Webtoon, heteronormativity, gender roles, homosexuality